Design of triangular MIMO antenna for 5G and beyond - Dwivedi S. (My University, 2025)
In this paper, design and simulation of high frequency antennas for 5G and beyond 5G have been proposed and investigated. This new era of 5G and beyond 5G are useful to connect most of the available devices and create a proper balance between systems and users as per demand of technology and requirement. For that purpose, a large bandwidth is supposed to be required with better gain. Hence, microwave frequency region 8 to 10 GHz has been explored for 5G and also 7 to 20 GHz is being explored for beyond 5G that is why both possibilities have been taken here. FR4 has been used as substrate material having capability of operating at both low and high frequency and also copper has been used for base material for design triangular shape array MIMO structure to achieve high gain. Structure is simulated with the help of CST microwave studio complete ground. Results obtained from these designs are -14.5dBi, -13.9dBi, 14.3dBi, 13.3dBi for all four ports excited separately or simultaneously. The S11 parameter is -72.82dB for frequency 9.3086GHz. Similar procedure has been used to simulate the single triangular structure with partial ground with gain of 10.5dBi. Few literatures survey has been discussed with evolution of beyond 5G technology. Also merit and demerit have been discussed for proposed structures. Bandwidth is increased from 0.29 GHz to 0.32 GHz. As many designed have already been discussed in section I and II, the new thing which is being introduced in this paper, a simple design, easy fabrication, low loss as it has no slots, available materials with simple feeding techniques. © 2024 IEEE.